A SILAC-based DNA protein interaction screen that identifies candidate binding proteins to functional DNA elements - Mittler, Gerhard; Butter, Falk; Mann, Matthias (Genome Research, 2009)
Determining the underlying logic that governs the networks of gene expression in higher eukaryotes is an important task in the post-genome era. Sequence-specific transcription factors (TFs) that can read the genetic regulatory information and proteins that interpret the information provided by CpG methylation are crucial components of the system that controls the transcription of protein-coding genes by RNA polymerase II. We have previously described Stable Isotope Labeling by Amino acids in Cell culture (SILAC) for the quantitative comparison of proteomes and the determination of protein–protein interactions. Here, we report a generic and scalable strategy to uncover such DNA protein interactions by SILAC that uses a fast and simple one-step affinity capture of TFs from crude nuclear extracts. Employing mutated or nonmethylated control oligonucleotides, specific TFs binding to their wild-type or methyl-CpG bait are distinguished from the vast excess of copurifying background proteins by their peptide isotope ratios that are determined by mass spectrometry. Our proof of principle screen identifies several proteins that have not been previously reported to be present on the fully methylated CpG island upstream of the human metastasis associated 1 family, member 2 gene promoter. The approach is robust, sensitive, and specific and offers the potential for high-throughput determination of TF binding profiles.